SkyMapper colours of Seyfert galaxies and changing-look AGN – II. Newly discovered changing-look AGN. Issue 1 (21st December 2021) - Hon, Wei Jeat; Wolf, Christian; Onken, Christopher A; Webster, Rachel; Auchettl, Katie
ABSTRACT: Changing-look active galactic nuclei (CLAGN) are AGN that change type as their broad emission lines appear or disappear, which is usually accompanied by strong flux changes in their blue featureless continuum. We search for turn-on CLAGN by selecting type-2 AGN from the spectroscopic Six-degree Field Galaxy Survey (6dFGS), whose colours, observed ∼15 yr later by the SkyMapper Southern Survey, are suggestive of type-1 AGN. Starting from 1092 type-2 AGN, we select 20 candidates for follow-up and confirm that 14 of them have changed into type-1 and are thus turn-on CLAGN; further observations reveal 11 more turn-on CLAGN. While our search was not tailored to efficiently discover turn-off CLAGN, we discover two such cases as well. The result suggests a turn-on CLAGN rate of over 3 per cent over ∼15 yr and imply a total CLAGN rate of more than ∼6 per cent over this period. Finally, we present observations of AGN that are atypical for the CLAGN phenomenology, including J1109146 – a type-1 that did not appear as an AGN at all in 6dFGS; J1406507 – the second reported changing-look narrow-line Seyfert 1; and J1340153 – a CLAGN with a change time-scale of 3 months.